School biographies of novice teachers in the English Teacher Training Program: professional dimension and the handcraft practice. (Praxis Educativa, 2017)
The flow of studies that aims at going deep into teaching practices to find the way through the maze is vast. For more than a century, we have been searching for the implications of teaching, trying to define the profession from different perspectives. American sociologist Richard Sennett (2009) has opened a line of investigation that seeks to understand teaching as handcraft labor. The author explains that artisanship is the ability to do things properly and that it exists because of a simple and lasting human desire: the wish of carrying out a task adequately. Being a craftsman implies, in a broad sense, a continuous monitoring of teaching practices for the sake of professional development. Turning into artisans of our own creation, committed to our job, brings us over with our coworkers. In the present work, we attempt to explore the professional dimension in the school biography of novice teachers from English Teaching Education at Universidad Nacional de Mar del Plata (UNMdP). We intend to lead a way that allows us to consider the teaching practices within a specific frame, the one of crafts.
Keywords: novice teachers; school biography; crafts.